Electronic Measurements of Single-Molecule Processing by DNA Polymerase I (Klenow Fragment). - Olsen, Tivoli J.; Yongki Choi; Sims, Patrick C.; Tolga Gul, O.; Corso, Brad L.; Chengjun Dong; Brown, William A.; Collins, Philip G.; Weiss, Gregory A. (Journal of the American Chemical Society, 2013)
Bioconjugating single molecules of the Klenow fragment of DNA polymerase I into electronic nanocircuits allowed electrical recordings of enzymatic function and dynamic variability with the resolution of individual nucleotide incorporation events. Continuous recordings of DNA polymerase processing multiple homopolymeric DNA templates extended over 600 s and through >10 000 bond-forming events. An enzymatic processivity of 42 nucleotides for a template of the same length was directly observed. Statistical analysis determined key kinetic parameters for the enzyme's open and closed conformations. Consistent with these nanocircuit-based observations, the enzyme's closed complex forms a phosphodiester bond in a highly efficient process >99.8% of the time, with a mean duration of only 0.3 ms for all four dNTPs. The rate-limiting step for catalysis occurs during the enzyme's open state, but with a nearly 2-fold longer duration for dATP or dTTP incorporation than for dCTP or dGTP into complementary, homopolymeric DNA templates. Taken together, the results provide a wealth of new information complementing prior work on the mechanism and dynamics of DNA polymerase I.